2015
DOI: 10.1111/apm.12362
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized high-density lipoprotein accelerates atherosclerosis progression by inducing the imbalance between treg and teff in LDLR knockout mice

Abstract: High density lipoprotein (HDL) dysfunction has been widely reported in clinic, and oxidation of HDL (ox-HDL) was shown to be one of the most common modifications in vivo and participate in the progression of atherosclerosis. But the behind mechanisms are still elusive. In this study, we firstly analyzed and found strong relationship between serum ox-HDL levels and risk factors of coronary artery diseases in clinic, then the effects of ox-HDL in initiation and progression of atherosclerosis in LDLR knockout mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…HDL increased the absolute numbers of Tregs in murine models (10). As HDL has also been shown to enhance the survival of endothelial cells in vitro (17), we thus evaluated the effect of HDL on the viability of purified Tregs…”
Section: Hdl Promotes Survival Of Tregs But Not Of Naïve or Memory Tmentioning
confidence: 99%
See 1 more Smart Citation
“…HDL increased the absolute numbers of Tregs in murine models (10). As HDL has also been shown to enhance the survival of endothelial cells in vitro (17), we thus evaluated the effect of HDL on the viability of purified Tregs…”
Section: Hdl Promotes Survival Of Tregs But Not Of Naïve or Memory Tmentioning
confidence: 99%
“…notably preventing atherosclerotic disease or pulmonary hypertension (8,9). This anti-inflammatory property could be at least partially mediated by an effect of HDL on Tregs, as splenic Treg counts in LDL receptor (LDLR) knockout mice increased after intraperitoneal injection of HDL/ ApoA-I (10,11). In addition, we recently showed that Treg frequency positively correlated with HDL-cholesterol (HDL-C) levels in healthy adults treated with statins (12).…”
mentioning
confidence: 99%
“…Ox-HDL has been detected in atherosclerotic plaques (11). It has been reported that ox-HDL exerts a cytotoxic effect on macrophages and accelerates atherosclerosis progression (12,13). However, the precise underlying mechanisms are poorly understood.…”
Section: Cell Culture and Sirna Transfectionmentioning
confidence: 99%
“…Limited studies utilizing highly sensitive liquid chromatography tandem mass spectrometry (LC-MS/MS), oxidized phospholipids (oxPLs) contained within Lp(a) have been shown to augment the pro-inflammatory response and promote CVD progression, an effect that was attenuated with inactivation of oxPLs 7 . Additionally, lower oxHDL also had pro-atherosclerotic effects and was accompanied by significant immunological responses 8 .…”
Section: Introductionmentioning
confidence: 99%